The Dark-Side of Rule Governed Behavior: An Experimental Analysis of Problematic Rule-Following in an Adolescent Population With Depressive Symptomatology. (July 2014) - McAuliffe, David; Hughes, Sean; Barnes-Holmes, Dermot
The current research set out to investigate whether adolescents who self-reported high or low levels of depressive symptomatology would demonstrate differential sensitivity to changing contingencies as a function of accurate/inaccurate (Experiment 1) or pliance/tracking instructions (Experiment 2). Following a screening procedure, students were divided into two groups and instructed on how to respond during a simple learning task. In Experiment 1, we observed a characteristic set of outcomes that were contingent upon the type of instructional control provided and levels of depressive symptomatology reported. Whereas accurate instructions resulted in quick and efficient learning (schedule sensitivity) regardless of depressive symptomatology, inaccurate instructions lead to problematic rule-following in the high depressive symptom group. Experiment 2 revealed that schedule insensitivity effects can be further augmented when participants who report depressive symptoms are equipped with a set of superordinate pliance instructions. In contrast, students in the tracking condition showed increasing adaptation to the changing contingencies throughout the study.